2018
DOI: 10.1029/2018ef000984
|View full text |Cite
|
Sign up to set email alerts
|

Interdependencies and Risk to People and Critical Food, Energy, and Water Systems: 2013 Flood, Boulder, Colorado, USA

Abstract: This paper examines the interdependencies mediating the cascading negative consequences triggered by the September 2013 flood, in Boulder, Colorado, USA. By illustrating the risks to people and critical food-energy-water systems of a low probability, high-impact event, we draw lessons on what is likely to occur in the future. Other scholars have modeled the influence of interdependent infrastructures on cascading effects. But this is one of the first studies integrating stakeholders' understanding of the influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…We found that FEW-nexus thinking is not yet embedded in city officials' narrative understandings of risk and planned adaptation actions, even when unpacking interdependencies among food, energy, and water systems may help cities tackle some of the root causes of vulnerability and risk (Romero-Lankao and Norton, 2018 ). Other scholars have already pointed to the fact that, while promising, FEW-nexus thinking faces many practical challenges.…”
Section: Adaptation Plans and Risk Inequalitymentioning
confidence: 98%
“…We found that FEW-nexus thinking is not yet embedded in city officials' narrative understandings of risk and planned adaptation actions, even when unpacking interdependencies among food, energy, and water systems may help cities tackle some of the root causes of vulnerability and risk (Romero-Lankao and Norton, 2018 ). Other scholars have already pointed to the fact that, while promising, FEW-nexus thinking faces many practical challenges.…”
Section: Adaptation Plans and Risk Inequalitymentioning
confidence: 98%
“…In total, the cities designed 51 actions with a primary focus on flood risks (either through a flood event or sea-level rise) and only 8 actions with a primary focus on some aspect of their coastal location outside of the context of a flood event. Miami, New York City, New Orleans, and Honolulu each had the most actions with a primary focus on flooding (13,8,6, and 6 actions, respectively), while Seattle had no actions relating to flooding. Seattle had four actions (1 primary focus, 3 partial focus) relating to non-flooding related aspects of the coastal environment related to the economic importance of their maritime lands and redoing their waterfront.…”
Section: Coastal Considerationsmentioning
confidence: 99%
“…There are many other factors outside of food-energy-water systems that can impact security in the face of hazards. As such, two studies advocate for using a framework that integrates the connections between the socio-demographic, economic, technological, environmental, and governance (SETEG) domains (Romero-Lankao & Norton, 2018;. Considering SETEG domains and their interdependencies allows cities to 'begin to anticipate and avoid cascading effects on WEF [water-energy-food] systems and resources' (Romero-Lankao et al, 2018, p. 221).…”
Section: Global Sustainabilitymentioning
confidence: 99%
“…Combining systems offers advantages such as, passing along waste, water, or nutrients for use in another system, combining resources and reducing demand for additional inputs thereby creating efficiencies. Redundant systems are important due to the cascading impacts that damage to one FEW system can have on the other (so that if one was damaged there was a redundant system available to keep operations running), such as was highlighted during the 2013 flood in Boulder, CO (Romero-Lankao & Norton, 2018). They highlight that since the city had backup generators (energy) they were able to keep the water treatment plant functional even though the broader energy system had been damaged by the flood (Romero-Lankao & Norton, 2018).…”
Section: Global Sustainabilitymentioning
confidence: 99%